Sterically demanding macrocyclic Eu(iii) complexes for selective recognition of phosphate and real-time monitoring of enzymatically generated adenosine monophosphate. Issue 12 (17th February 2022) - Bodman, Samantha E.; Breen, Colum; Kirkland, Sam; Wheeler, Simon; Robertson, Erin; Plasser, Felix; Butler, Stephen J.
Abstract : We present two new europium-based anion receptors that selectively bind to inorganic phosphate and AMP in aqueous media. Their sensing selectivity follows the order AMP > ADP > ATP, representing a reversal of the selectivity order observed for most nucleoside phosphate receptors. Abstract : The design of molecular receptors that bind and sense anions in biologically relevant aqueous solutions is a key challenge in supramolecular chemistry. The recognition of inorganic phosphate is particularly challenging because of its high hydration energy and pH dependent speciation. Adenosine monophosphate (AMP) represents a valuable but elusive target for supramolecular detection because of its structural similarity to the more negatively charged anions, ATP and ADP. We report two new macrocyclic Eu(iii ) receptors capable of selectively sensing inorganic phosphate and AMP in water. The receptors contain a sterically demanding 8-(benzyloxy)quinoline pendant arm that coordinates to the metal centre, creating a binding pocket suitable for phosphate and AMP, whilst excluding potentially interfering chelating anions, in particular ATP, bicarbonate and lactate. The sensing selectivity of our Eu(iii ) receptors follows the order AMP > ADP > ATP, which represents a reversal of the order of selectivity observed for most reported nucleoside phosphate receptors. We have exploited the unique host–guest induced changes in emission intensity and lifetime for the detection of inorganic phosphate in human serum samples, and for monitoring the enzymatic production of AMP in real-time.